Stylistics in Negeri Para Bedebah Novel (Figure of Speech, Dictions, Morphologhical) - Indira Ginanti; Ikhwanuddin Nasution; T. Thyrhaya Zein (Budapest International Research and Critics University, 2022)
This study describes the use of stylistics in the novel Negeri Para Bedebah by Tere Liye. This research is a descriptive qualitative research. The data collection method used in this study is the documentation method using an interactive model that applies four stages, including: data collection, data condensation, data presentation, and drawing conclusions, and reviewing. The selected data are data that can be analyzed based on figure of speech, the use of diction, and morphological aspects. The results of this study are to describe the data relating to: (1) the use of language style based on figure of speech and its function, namely: 1) repetition; 2) comparative language style; 3) contradictory language style; 4) linking language style; (2) The use of language style based on the use of diction and its function; (3) The use of language style based on morphological aspects and their function, which consists of affixation, reduplication, and compounding.